(untitled) (Bangladesh Journal of Scientific Research, 2012)
Key words: Natural language processing; C4.5 classification; DSS, machine learning; KNN clustering; SVM DOI: http://dx.doi.org/10.3329/bjsr.v24i2.10768 Bangladesh J. Sci. Res. 24(2):117-126, 2011 (December)